Analisis Cadangan Kerugian Penurunan Nilai (CKPN), Return On Asset (ROA) Dan Return On Equity (ROE) Pada Bank BUMN - Darmawati, Wissa (IJAcc, 2025)
The background of this research is motivated by the implementation of the new accounting standard, PSAK 71, along with the impact of the COVID-19 pandemic, which has resulted in increased credit risk and a rise in Non-Performing Loans (NPL). These developments pose significant challenges to the banking sector, which serves as a primary pillar of the economy, as rising credit risk reflects the financial difficulties faced by individuals and businesses. This study employs the variables Allowance for Impairment Losses (CKPN), Return on Assets (ROA), and Return on Equity (ROE). The sample includes four state-owned banks (BUMN) listed on the Indonesia Stock Exchange, namely BRI, Bank Mandiri, BNI, and BTN, covering the period from 2019 to 2023. The findings reveal that the average CKPN of the four banks falls into the Special Mention category. For the ROA variable, two banks—BRI and Bank Mandiri—are classified as Very Healthy, BNI is classified as Healthy, while BTN is categorized as Fairly Healthy. Regarding the ROE variable, BRI and Bank Mandiri are classified as Fairly Healthy, whereas BNI and BTN fall into the Less Healthy category. Keywords: Allowance for Impairment Losses (CKPN), PSAK 71, Return On Assets (ROA), Return On Equity (ROE)